2018
DOI: 10.1103/physrevb.97.155412
|View full text |Cite
|
Sign up to set email alerts
|

Valley qubit in a gated MoS2 monolayer quantum dot

Abstract: The aim of presented research is to design a nanodevice, based on a MoS2 monolayer, performing operations on a well-defined valley qubit. We show how to confine an electron in a gate induced quantum dot within the monolayer, and to perform the NOT operation on its valley degree of freedom. The operations are carried out all electrically via modulation of the confinement potential by oscillating voltages applied to the local gates. Such quantum dot structure is modeled realistically. Through these simulations w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 79 publications
0
53
0
Order By: Relevance
“…Recently, semiconducting 2D transition metal dichalcogenides (TMDCs) have attracted interest as potential material systems for quantum dots. Based on the strong spin‐orbit coupling, leading to a spin‐split band structure, multiple types of electronic qubits, utilizing spin and valley degrees of freedom, have been proposed . Unlike III–V semiconductors, TMDCs in principle allow zero nuclear spin materials, avoiding hyperfine interactions with the electron spin.…”
mentioning
confidence: 99%
“…Recently, semiconducting 2D transition metal dichalcogenides (TMDCs) have attracted interest as potential material systems for quantum dots. Based on the strong spin‐orbit coupling, leading to a spin‐split band structure, multiple types of electronic qubits, utilizing spin and valley degrees of freedom, have been proposed . Unlike III–V semiconductors, TMDCs in principle allow zero nuclear spin materials, avoiding hyperfine interactions with the electron spin.…”
mentioning
confidence: 99%
“…Finally on top of the sandwiched structure we lay down four 15 nm wide control gates (G 1.. 4 ), placed symmetrically around the central square-like gap of size 20×20 nm. The gate layout presented here is quite similar to the one proposed by us recently [3], but with a larger 20 nm clearance between opposite gates, which may ease their deposition.…”
Section: Device Structurementioning
confidence: 64%
“…MoS 2 , seem to be better candidates than graphene because of their wide band gaps and strong electrically induced spin-orbit coupling of the Rashba type [1,2]. By considering the valley degree of freedom of an electron together with its spin we extend our ability to define a qubit into: spin, valley [3] and hybrid spin-valley qubit [4]. However, the most interesting is the definition based on spin and valley of a single electron as a two-qubit system [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A recipe for a CNOT gate with these states is readily available from the original Loss and DiVincenzo proposal for spin-only qubits [46]. If, in addition, the τ x operation could be effectively implemented (theoretical proposals to achieve this include the use of impurities [35,61] or the use of oscillating confinement potentials [36]), then we would also have a full set for single qubit operations. Moving to the asymmetric spin-orbit splitting we found that only the exchange energy is affected, while the form of the exchange Hamiltonian remains unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Although these two features are common to several other systems used for QDs, such as Si/SiGe quantum wells [13][14][15][16], graphene [17][18][19][20][21][22] and carbon nanotubes (CNTs) [23][24][25][26], TMDCs are special because they exhibit very strong spin-orbit coupling (SOC). Theoretical investigation of QDs in TMDCs started with QDs in gated nanoribbons [27] and the magnetic field dependence of the single-electron spectrum [7] and it now includes studies of valley hybridisation [28], flake QDs of triangular and hexagonal shape and nanoribbons [29,30], the valley Zeeman effect [31], optical control of a spin-valley qubit [32], spin-degenerate regimes for small QDs in a magnetic field [33], spin relaxation [34], electric control of a spin-valley qubit [35] and a model of valley qubit [36]. On the experimental side, gating monolayer TMDCs is not straightforward [38,40] and low material quality has hindered the exper imental study of the intrinsic properties of these mat erials for a long time.…”
Section: Introductionmentioning
confidence: 99%